2015
DOI: 10.1007/s11146-015-9541-0
|View full text |Cite
|
Sign up to set email alerts
|

Commission Splits in Real Estate Transactions

Abstract: We examine commission splits between listing and selling agents in real estate transactions. We construct a theoretical model to show that agency problems arise when a listing agent attempts to maximize his or her payoff while setting the commission split. Mitigation to these agency problems can be achieved through the imposition of a limited duration on listing contracts. Our model produces several testable hypotheses, which are supported by empirical evidence. We find property listings with higher list price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…They find that houses listed by discount brokers sell for the same prices as other houses, but are less likely to sell, and stay about three days longer on the market. Bian, Waller and Yavas () examine commission splits between listing and selling agents and show that an additional agency problem arises when the listing agent sets the commission split. Li and Yavas () study an agency model of real estate brokerage with multiple agents, and find that, from a social planer's perspective, the current commission rate of 5–7% is too high and the commission split is too much in favor of the seller's agent.…”
Section: Literaturementioning
confidence: 99%
“…They find that houses listed by discount brokers sell for the same prices as other houses, but are less likely to sell, and stay about three days longer on the market. Bian, Waller and Yavas () examine commission splits between listing and selling agents and show that an additional agency problem arises when the listing agent sets the commission split. Li and Yavas () study an agency model of real estate brokerage with multiple agents, and find that, from a social planer's perspective, the current commission rate of 5–7% is too high and the commission split is too much in favor of the seller's agent.…”
Section: Literaturementioning
confidence: 99%
“…The only shift is when price points were too low to generate any significant percentage-based commission. Most recently, Bian et al (2017) became the first to examine listing agents' incentives to set commission splits, also known as the cooperative commission. They found that listing agents tend to offer a lower commission split when listing a more expensive property and that listings with higher list prices and quick sales tend to have lower cooperative commissions.…”
Section: Introductionmentioning
confidence: 99%
“…The only shift is when price points were too low to generate any significant percentage-based commission. Most recently, Bian et al . (2017) became the first to examine listing agents' incentives to set commission splits, also known as the cooperative commission.…”
Section: Introductionmentioning
confidence: 99%